Resistências, desafios e avanços na implementação da Educação das Relações Étnico-Raciais na rede municipal de Sorocaba (SP): uma análise a partir dos dispositivos - Carvalho, Érika Fernanda Monteiro de (2025)
This study analyzes how the city of Sorocaba/SP has implemented education on ethnic-racial relations and the teaching of Afro-Brazilian and African history and culture, in accordance with Articles 26-A and 79-B of the Brazilian Law of Guidelines and Bases of National Education (LDB) 9.394/96 and the National Curricular Guidelines for the Education of Ethnic-Racial Relations (DCNERER), focusing on early years elementary education. The research examines documents and initiatives under municipal responsibility based on the provisions of Federal Law 10.639/03, including the municipal education plan, local legislation, school curriculum guidelines, pedagogical planning directives, and municipal forums dedicated to ethnic-racial education, all within the scope of Sorocaba’s Municipal Department of Education. The analysis reveals institutional challenges, such as the persistent absence of comprehensive educational policies over the years. Although some initiatives have been implemented, they are largely the result of tensions and pressures exerted by the local Black movement, underscoring the difficulties in enforcing the DCNERER. The study concludes by emphasizing the urgent need for consistent public educational policies, institutional support, teacher training, and appropriate teaching materials to effectively address racism in the municipality.